Prevalence and risk factors related to neurocysticercosis in workers of camal Conchucos, Perú - Solís Quispe, Ana M. (2024)
Introducction: neurocysticercosis is the most common parasitic disease of the Central Nervous System in Perú; it is hyperendemic in the Highlands and also in some areas of the Coast and Jungle.Objectives: To determine the prevalence and risk factors related to neurocysticercosis in workers of a slaughterhouse in an impoverished area of Lima.Materials and methods: this is a transversal study in 60 workers of a slaughterhouse in the capital of Perú; the workers underwent a clinical, epidemiological and serological (EITB) evaluation; an axial computer tomography was obtained from those who were EITB positive. The O.H Del Brutto (1996) neurocysticercosis diagnostic criteria were used. The prevalence of neurocysticercosis and its association with risk factors were calculated with the SPSS statistical package, v 10.0.Results: the prevalence of neurocysticercosis in our study was 1.7% and the cysticercosis seroprevalence was 15%. Among the risk factors, those which had a greater association with EITB positive patients were: inadequate hygienic habits and lack of sewage services; the ORs were 11.6 and 2.14 respectively.Conclusions: the prevalence of neurocysticercosis (1.7%) in our study was less than that found in autopsies of Peruvian adults (3.1%). The seroprevalence found (15%) is quite similar to that found in endemic areas of Perú and in countries like Mexico (10.8%), Ecuador (21.4%) and Colombia (19.6%). The lack of knowledge of these people on the mechanisms of neurocysticercosis transmission and of means for its prevention may explain the association with the risk factors mentioned.